The Tragic Tale of Claire Ferchaud and the Great War - Jonas, Raymond Anthony (Book collections on Project MUSE., 2005)
This is the moving and improbable story of Claire Ferchaud, a young French shepherdess who had visions of Jesus and gained national fame at the height of World War I as a modern-day Joan of Arc. From her modest origins to her spectacular ascent, Claire's life and times are deftly related with literary verve and insight in a book that gives a rare view of the French countryside during the Great War. Claire experienced her first vision of Jesus after a childhood trauma in which her mother locked her in a closet to break her stubborn willfulness. She developed her visionary gifts with the aid of.